Neural Correlates of Visuospatial Attention to Unseen Stimuli in Hemianopic Patients. A Steady-State Visual Evoked Potential Study - Sanchez-Lopez, Javier; Savazzi, Silvia; Pedersini, Caterina Annalaura; Cardobi, Nicolò; Marzi, Carlo Alberto (Frontiers in Psychology, 2019)
The relationship between attention and awareness is a topic of great interest in cognitive neuroscience. Some studies in healthy participants and hemianopic patients have shown dissociation between these two processes. In contrast, others confirmed the classic notion that the two processes are mutually exclusive. To try and cast further light on this fascinating dilemma, in the present study we have investigated the neural mechanisms of visual spatial attention when perceptual awareness is totally lacking. To do that, we monitored with steady-state visual evoked potentials (SSVEPs) the neurophysiological correlates of endogenous spatial attention to unseen stimuli presented to the blind field of hemianopic patients. Behaviourally, stimulus detection (a brief change in the orientation of a gabor grating) was absent in the blind hemifield while in the sighted field there was a lower, but non-significant, performance in hit rate with respect to a healthy control group. Importantly, however, in both blind and sighted hemifield of hemianopics (as well as in healthy participants) SSVEP recordings showed an attentional effect with higher frequency power in the attended than unattended condition. The scalp distribution of this effect was broadly in keeping with the location of the dorsal system of endogenous spatial attention. In conclusion, the present results provide evidence that the neural correlates of spatial attention are present regardless of visual awareness and this is in accord with the general hypothesis of a possible dissociation between attention and awareness.